Strategi Pengelolaan Bisnis Kecantikan Berbasis Kualitas Layanan dan Digital Marketing dalam Mempertahankan Loyalitas Pelanggan: Studi Kasus pada Lydia Beauty Salon di Semarang - Septia Puja Mulia; Aniq Muyasyaroh; Angelly Rahmadania Putri Kedua; Tiara Agni Prameswari; Sri Endah Wahyuningsih (Educatoria : Jurnal Ilmiah Ilmu Pendidikan, 2026)
The beauty industry in Indonesia has experienced rapid growth in line with increasing public awareness of self-care, skin health, and appearance. Intensifying competition has prompted beauty business operators to implement effective management strategies to retain customers and ensure business sustainability. This study aims to analyze beauty business management strategies in enhancing customer loyalty at Lydia Beauty Salon. The research design is descriptive qualitative using a case study method. The research informant consists of 1 beauty business owner. The research subjects include service quality strategies, digital marketing, and customer loyalty. Data collection techniques included observation, interviews, and documentation, while data analysis utilized data reduction, data presentation, and drawing conclusions. The results indicate that service quality, the use of digital marketing, service innovation, and customer loyalty programs positively contribute to customer satisfaction and loyalty. This study is expected to serve as a reference for beauty business operators in developing sustainable business strategies.